MOBILE BANKING SYSTEM DEVELOPMENT USING NEAR FIELD COMMUNICATION TECHNOLOGY WITH ANDROID-BASED OPERATING SYSTEM - Bisri Nursa Fadillah; Dewi Khairani; Nurul Faizah Rozi (JURNAL TEKNIK INFORMATIKA, 2020)
Development of information technology (IT) is used to support business sector, including banking. One of them, banking uses IT to improve the quality of service in the form of internet banking and mobile banking. Therefor, the research focused on development of mobile banking system using Near Field Communication (NFC) technology as client authentication and security system. Features on mobile banking system are checking balance information, mutation, electricity bill, a fellow bank transfer and transfers between Bank that has been working with ATM Bersama, as well as payment of electricity bills. System development using JAVA programming language with Android Studio tools, to access server using PHP with MySQL as database management, IdWebHost as hosting services, as well as data output using JSON format. Data collection method is done with interview stage and literature study. Researcher uses system development methods of Rapid Application Development (RAD), while testing using unit testing and user acceptance testing. Result of the study is secure mobile banking system utilizing Near Field Communication technology, PIN, and AES encryption.